Benchmarking of quantum gate decomposition frameworks - Verma, Dev (Nanyang Technological University, 2025)
As quantum algorithms grow in sophistication, so does the need to compile them into gate sequences that today’s quantum hardware can actually execute. This thesis explores the problem of quantum gate decomposition — the process of translating high-level unitaries into low-level gates — by benchmarking the performance of two prominent frameworks: Qiskit and Classiq. Focusing on operations central to quantum algorithms, including Multi-Controlled X (MCX) gates, Grover operators, and Haarrandom unitaries, we compare how each framework performs under varying resource constraints and optimization settings.